A Mislocated Intrauterine Device Migrating to the Urinary Bladder: An Uncommon Complication Leading to Stone Formation - Mohamed Ali Nouioui; Tarek Taktak; Seif Mokadem; Houssem Mediouni; Ramzi Khiari; Samir Ghozzi (Case Reports in Urology)
Intrauterine devices are a popular form of reversible contraception among women. Its administration can lead to some uncommon but serious complications such as perforation leading to its migration into adjacent organs. Like any foreign body, the presence of an IUD in the bladder can result in stone formation due to its lithogenic potential. We report a case of an IUD migrating from its normal position in the uterine cavity into the urinary bladder causing chronic low urinary tract symptoms in a 43-year-old female patient. The device was securely removed without complications using grasping forceps under cystoscopy, and no parietal defect was detected. A mislocated IUD is a rare complication that should be considered in female patients presenting with chronic urinary symptoms.